Ruptured blister like aneurysm with satisfactory management using remodeling technique – Case report - Vargas Urbina, John F. (2022)
Introduction: Blister-like aneurysms are small, complex, smaller than 3mm, with high rate of morbidity and mortality, as well as rebleeding and recurrence. They are difficult to treat and microsurgical and endovascular techniques are current treatment modalities. Endovascular technique has the lowest rate of complications. Clinical case: 74-year-old woman, admitted with 6 hours of sudden sensory disorder. The CT scan shows diffuse subarachnoid hemorrhage predominantly on the left side. A cerebral angiography showed a blister-like aneurysm of the left middle cerebral artery trifurcation. The patient was treated with coiling and remodeling technique, achieving a complete occlusion. Conclusion: Blister-like aneurysms are complex and rare, whereas endovascular therapy is a safe and effective alternative with low complication rate.